THE IMPORTANCE OF FORMING READING LITERACY IN PRIMARY CLASS STUDENTS - Nafisa Saidakhmadova, (International Journal of Innovations in Engineering Research and Technology, 2023)
The article describes the theoretical foundations of the formation of reading literacy in elementary school students, as well as teaching students to read consciously, correctly and expressively, to develop the culture of reading and speech, and the ability to think independently.